2013
DOI: 10.1007/s10489-013-0458-0
|View full text |Cite
|
Sign up to set email alerts
|

An optimization algorithm inspired by the States of Matter that improves the balance between exploration and exploitation

Abstract: The ability of an Evolutionary Algorithm (EA) to find a global optimal solution depends on its capacity to find a good rate between exploitation of found-so-far elements and exploration of the search space. Inspired by natural phenomena, researchers have developed many successful evolutionary algorithms which, at original versions, define operators that mimic the way nature solves complex problems, with no actual consideration of the explorationexploitation balance. In this paper, a novel nature-inspired algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(89 citation statements)
references
References 56 publications
0
88
0
1
Order By: Relevance
“…The success of the metaheuristic optimization algorithm depends on the balance between the algorithm's exploration (diversification) and exploitation (intensification) capability [44,[60][61][62][63]. This study proposes variable changing methods for the CDI and MDI of SBX and PM, respectively.…”
Section: Variable Exploration and Exploitation Balancing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the metaheuristic optimization algorithm depends on the balance between the algorithm's exploration (diversification) and exploitation (intensification) capability [44,[60][61][62][63]. This study proposes variable changing methods for the CDI and MDI of SBX and PM, respectively.…”
Section: Variable Exploration and Exploitation Balancing Approachesmentioning
confidence: 99%
“…However, some studies reported that the balance should be variable to guarantee the best performance [41][42][43] because the effectiveness of wide search and fine-tuning depends on the optimization phase. Cuevas et al [44] stated that a common strategy for balancing exploration and exploitation is to start with exploration and then gradually increase exploitation as good fitness points are identified. It would be a better strategy in the automatic calibration of a hydrological model to focus on searching various parameter sets broadly in the early optimization phase and to give more weight to fine-tuning the solutions found in the latter phase.…”
Section: Introductionmentioning
confidence: 99%
“…The steepest descent direction is used to change the direction of modification. The equation is defined as in (5).…”
Section: Proposed Approachmentioning
confidence: 99%
“…That is, direction for the best estimator that a particle has ever reached, direction for the best one that all particle have ever found and momentum are successfully combined to determine the next iteration. Unfortunately, PSO show some weakness in term of balance between exploitation and exploration during the search [5]. For example in multi-objective problems, the search is not concentrated on the visited areas effectively, and often it shows a premature convergence and lack of diversification during moving from position to another.…”
mentioning
confidence: 99%
“…Two essential common characteristics of these different meta-heuristics are exploration and exploitation. Besides, there are also other heuristic algorithms [6][7][8][9] to solve the optimization problem. Further more, this paper design a new meta-heuristic algorithm, which is named as beetle antennae search (BAS) algorithm to solve the optimization problems, taking inspiration from detecting and searching behavior of long-horn beetles.…”
Section: Introductionmentioning
confidence: 99%